Development and use of GIS database for tasks of normative monetary evaluation of land of settlements - Trofymenko, P.; Tretyak, A.; Bezgodkova, Yu.; Trofimenko, N.; Zatserkovnyi, V. (Land Management, Cadastre and Land Monitoring, 2021)
The paper presents the results of research on the development of a GIS database for the tasks of normative monetary valuation of lands of settlements and highlights the applied aspects of its use on the example of Lychanka village, Dmytriv territorial community, Bucha district, Kyiv region.An algorithm for developing a GIS database for normative monetary valuation of settlement lands is presented. The presented estimation algorithm allows to carry out with high accuracy normative monetary estimation of settlements, to carry out its automated updating on a certain date, to receive necessary information on request, to carry out analytical operations and construction of specialized estimation maps.The development of the GIS database involved the implementation of two stages. At the first stage of formation of the initial land assessment base, the attribute table included data from the Public Cadastral Map of Ukraine on land plots within the settlement by the following items: cadastral number of land plot, area, form of ownership, purpose and functional use of land plot , the number of the cadastral zone in which each land is located, the number of the land assessment area of the settlement, the value of the base value of land, the value of the zonal coefficient (Km2), the coefficient characterizing the functional purpose of the land (Kf), information on the location (street name). The second stage involved the calculation of the value of the normative monetary valuation of each of the 1279 land plots and was performed using the built-in Arc Map function "Calculation of numerical values".After the development of the GIS database, the testing stage of the developed land assessment database was performed, which involved the use of various query execution, geospatial analysis, the use of buffering functions, topological overlay (intersection).As a result of the analysis, the following maps were constructed: "Influence of local factors on the distance of land from the center of the settlement", "Influence of local factors on the distance of land from highways", "Influence of local factors on the environmental situation", "Influence of local factors on security electricity", "Influence of local factors on the distance from paved roads", "Influence of local factors on the provision  of centralized water supply", "Influence of local factors on the provision of centralized sewerage", "Influence of local factors on the provision of centralized gas supply", "Map plots according to the results of normative monetary assessment" , "Map of the establishment of buffer zones by the value of local coefficients" , "Map of coastal protection strips around water bodies with the allocation of zones of their intersection with land".Due to the application of special functions of geospatial analysis available in the GIS environment, examples of development of highly informative cartographic materials in the form of special pricing zoning of the territory of the settlement are shown. The expediency of the application of the GIS database for the tasks of monitoring the quality of land, compliance with their legal regime and the possibility of monitoring the implementation of fiscal obligations by landowners and users.Key words: normative monetary valuation, GIS database, geospatial analysis, buffering, land valuation zoning, maps.